(3eMGSHI GdJcGdja (B/s - (3YHO GdSdGe, Cjef jhSas ((3YeGf(B: s (3OGQ ZjOGA ddfTQ hGdJhRjY(B, s, 2019)
(3eaghe hCgOGa fXGe GdJcGdja, fXGe GdJcGdja Ydi CSGS GdGfTWI GdehLgI , CSGSjGJ eMGSHI GdJcGdja, WQb hJUfja HfhO GdJcdaI, GdJcGdja GdUfGYjI ZjQ GdeHGTQI, JMdjd GdJcGdja GdeGdjI ddeDSSGJ GdUMjI JCKjQ GdJcGed Hjf GdJbfjGJ GdeSJLOI aj eMGSHI GdJcdja hJQGHWgG aj GdNOeI, GdeMGSHI aj GdefTBJ GdUfGYjI, GdeMGSHI GdEOGQjI aj eLGd GdQbGHI hJbjje GdCOGA, GdLeYjGJ GdegfjI GdOhdjI hCKQgG Ydi JWhjQ GdfXGe GdeMGSHj, CSGSjGJ eMGSHI GdJcGdja aj GdefTBJ GdUfGYjI, CKQ JNajV GdJcGdja Ydi JfGaSjI GdeDSSI, GdJcGdja GdeHGTQI heTGcdgG hWQb JMejdgG, eMGSHI GdJcGdja aj GdfTGW GdafObj, GdeNRhf, eONd ebJQM dJWhjQ OhQ GdeYdheGJ GdeMGSHjI(B.s
(3HjHdjhZQGajG(B: (3U U(B.465-477s
Keywords: (3GdTQcGJ(B- (3GdeMGSHIs; (3eMGSHI GdJcGdjas